Budaya Organisasi, Kejelasan Sasaran Anggaran, Sistem Pelaporan dan Akuntabilitas Kinerja Instansi Pemerintah - Dhevi Sukma Dewi, Ni Wayan; Alit Suardana, I Ketut (E-Jurnal Akuntansi, 2020)
Public accountability and openness are part of good governance principles. The aim of this research is to know the influence of organizational culture, the clarity of budget targets, and the reporting system on the performance accountability of Badung Regency OPD. The research methods used are survey methods by spreading questionnaires to the Head of OPD, Head of Sub Division of General and Planning, and Head of Sub Division of Financial and Accounting. The data analysis technique used is multiple linear regression. The results showed that the clarity of the budget target was positively influential in performance accountability. Meanwhile, organizational culture and reporting systems negatively affect performance accountability. Keywords: Organizational Culture; Clarity Of Target Budgets; Reporting System; Government Agency Performance Accountability.